(untitled) (Global Conference on Medical and Health Sciences, 2026)
This article presents a systematic literature review examining the impact of electronic health records (EHRs) and clinical decision support systems (CDSS) on quality of care and patient safety. Publications from 2010 to 2024 indexed in PubMed, Scopus, Web of Science, and the Cochrane Library were analysed. The review covers EHR adoption patterns and implementation challenges, clinical decision support functions and their evidence base, medication safety applications, preventive care improvement, and the challenges of interoperability and clinical workflow integration. The analysis demonstrates that well-implemented EHR systems with integrated CDSS reduce preventable adverse drug events by 40–80%, improve adherence to clinical guidelines by 15–25%, and decrease duplicate test ordering by 10–20%, generating measurable quality and safety improvements. However, the realisation of these benefits depends critically on system usability, clinical workflow integration, and clinician training quality. The implications for health information system development in Uzbekistan are examined.